Carbon emission forensic in the energy sector: Is it worth the effort?. (May 2019) - Chen, Yihsu; Zhang, Duan; Takashima, Ryuta
Abstract: Climate policy has mostly focused on regulating power suppliers. There is a growing interest in exploring regulating emissions from the demand side by incentivizing consumers to reduce their energy consumptions, or to purchase power from cleaner sources through tracking carbon content of power flow in the transmission network. This paper analyzes market outcomes under two approaches: producer-based and demand-based carbon taxes. We formulate each approach as a market equilibrium model. For the consumer-based approach, the analysis assumes that a utility, procuring electricity on behalf of consumers, is subject to the carbon tax. For the producer-based approach, the producers are subject to the carbon tax, and therefore, pay for their emissions. We show that the two approaches are equivalent when the program's coverage is complete. However, when the coverage is incomplete, the consumer-based carbon tax is less effective in pricing carbon emissions owing to the fact that sales to unregulated regions are not subject to the carbon tax. Given that the transaction cost of implementing consumer-based tax is likely to be high, benefit of tracking power flows in order to estimate carbon content or footprint might not be justified even with a full coverage program. Abstract : Highlights: We examine the market outcomes of a consumer-based and a producer-based carbon tax. We show that the two approaches are equivalent when coverage is complete. We demonstrate possibility of emission leakage under a consumer-based policy. A consumer-based policy is likely to incur a higher transaction cost and thus less efficient.